PEMBUATAN SISTEM INFORMASI PARIWISATA DAERAH ISTIMEWA YOGYAKARTA BERBASIS ANDROID - , AQIL RAHMATULLAH; , Dr.Eng. Purnama Budi Santosa, ST, M.App.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta is one of the most popular destination cities for local and international tourist. It is commonly well known for its natural splendors, art, and culture. The development of information technology has contributed to the easy access to tourism information. Many web developers have tried to develop an interesting website and users-friendly websites related to information about Yogyakarta tourisms. In 2008, the first Android-based smartphone was released. Android is an open source operating system. The ease of getting Android OS provides a great opportunity to mobile phone users to migrate from a web-based application. Android OS-based mobile web can be used to exchanges information as an improvement of the existing facilities on the fixed web. Smartphones with Android OS can be used as a tool to deliver tourism information and to support what tourists need when they will make a journey. The purpose of this research is to develop a tourism information system of Yogyakarta based on Android OS which displays the position of tourist areas and can be used easily by users. The data of the research were collected from the tourism data of Yogyakarta in 2012, as well as others data which were retrieved from Yogyakarta tourism websites. The system development process consists of several steps, includes : setting up the server part which is functioned as a mediator between Android and server